Do developmental milestones at 4, 8, 12 and 24 months predict IQ at 5–6 years old? Results of the EDEN mother–child cohort. (March 2017) - Peyre, Hugo; Charkaluk, Marie-Laure; Forhan, Anne; Heude, Barbara; Ramus, Franck; ,
Abstract: Rationale: The present study aims: ( i ) to determine how well developmental milestones at 4, 8, 12 and 24 months may predict IQ at 5–6 years old, ( ii ) to identify cognitive domains during the first two years that best predict later IQ and ( iii ) to determine whether children with IQ in the normal range at 5–6 years old may differ from disabled (IQ < 70) and gifted children (IQ > 130) with regard to their early cognitive development. Method: The main developmental milestones were collected through self-administered questionnaires rated by parents at 4, 8, 12 and 24 months and through parental questionnaires administered by a trained interviewer and questionnaires completed following a medical examination at 12 months. These questionnaires were derived from the Brunet-Lézine Psychomotor Development Scale and they addressed several cognitive domains (gross and fine motor skills, language and socialization). Results: ( i ) Developmental milestones predict a substantial part of the later IQ variance from 24 months (R 2 ∼ 20%). ( ii ) Early language skills more strongly predict later IQ than the other cognitive domains. ( iii ) Several cognitive domains, but particularly language skills, predict disabled children at 5–6 years old (from the age of 8 months) and gifted children (from the age of 12 months). Discussion: The present study provides valuable information for early developmental assessment and could contribute to a better understanding of intellectual development. Highlights: Children who had not reached a milestone acquired by 90% of the children of the same age scored. 2.5 IQ points lower when milestones were assessed at 4 and 8 months. 5 IQ points lower when assessed at 12 months. 8 IQ points lower when assessed at 24 months. Early milestones in the language domain were those that best predict intelligence at 5–6 years old.